Millitating Factors On The Efficient Management Of Students’ Record Among Registry Staff In Academic Institutions (A Case Study Of Babcock University) - Allison, Goodluck Okwudiri; Otuza, Chima Evans (Advances in Social Sciences Research Journal, 2017)
Management of students’ records is crucial to all universities as they rely on their information for future decision making and university growth; unfortunately in Nigerian universities today, it seems little or no attention is given to students’ record management especially in registry which is the bedrock of students’ records. This study examined the factors affecting efficient management of students’ record among record management personnel in Babcock University. A survey design was employed for the study. The population consisted of all the registry staff of Babcock University with a total number of 102 staff who served as the sample for the study. A self-structured questionnaire titled (FAEMSR) with the Likert four point scale in order of strongly Agree = 4, Agree = 3, disagree = 2, strongly Disagree = 1, and two point scales of yes or No and Attended or Not Attended were used to gather data validated with overall Cronbach alpha reliability coefficient of 0.97; all the staff participated in the study and subsequently, the study was analyzed using descriptive statistics. Findings certified that there is little number of staff in the registry with records management qualification or with related courses. It also show negative factors associated with efficient management of students’ records in Babcock University as: negative attitude of staff, badly implemented record management system, insecurity of records, use of paper convention, lack of training, manual operation, inadequate computer terminal and resources to ineffective retrieving, retention and disposition schedule, as well as lack of policy and filing procedure manual. The study concluded that a major factor that militate against efficient management of students’ record rests on the fact that high number of personnel in the registry are yet to have requisite qualifications in records management to work in registry. Therefore, the study recommended that all registry staff should have basic qualifications in records management or related fields, and a regular training be carried out on a semester basis for all the personnel in the department.